Suspected aspirin resistance in individual healthy adult warmblood horses. Issue 6 (7th April 2017) - Roscher, K. A.; Failing, K.; Schenk, I.; Moritz, A.
Abstract : The reasons for this prospective experimental study were to determine a dosing scheme with loading and maintenance dose of aspirin inducing inhibition of platelet function measured by whole blood impedance aggregometry. Ten horses received aspirin orally in the morning with one loading dose of 4.7–5 mg/kg and maintenance doses of 1–1.3 mg/kg daily the following 4 days. Aggregometries (COLtest, ASPItest, ADPtest) and serum salicylic acid were measured. ASPItest showed significant difference in inhibition at 24 and 48 hr ( p < .05) and 96 hr ( p < .01). Significant change for ADPtest and COLtest couldn't be detected. Serum salicylic acid concentrations were significantly ( p < .01) increased at 6 and 12 hr. Despite this, three horses failed any inhibitory effect of platelet function, suspecting an aspirin resistance. Regarding the other seven horses platelet aggregation induced by ASPItest was reduced between 37% and 100% from baseline at 6 and 12 hr and between 0 and 98% during the next 4 days. Correlations of serum concentration of salicylic acid and aggregometries couldn't be detected. It can be presumed that equine platelets are less susceptible to aspirin what may compromise eventually the anticoagulatory effects and efficacy in preventing and treating diseases with increased platelet activation as endotoxaemia or laminitis.